從「無感」到「五感」的環境意識啟蒙：特定場域劇場教學之批判教育學實踐 From “Indifference” to Environmental Conscientization Through Critical Sensory Pedagogy: A Critical Pedagogy Praxis in a University Site-Specific Theatre Class - 藍貝芝 Betsy Lan; 楊佳羚 Chia-Ling Yang (臺灣教育社會學研究)
本研究為聚焦「年輕公民與社會／生態正義」跨國研究案的臺灣個案研究，於某大學表演相關科系執行以環境與氣候變遷為主題的「特定場域劇場」戲劇課程。本研究問題有二：如何將批判教育學具體實踐於戲劇教育課程？如何透過聚焦氣候與環境正義的戲劇課程，激發學生的批判思考，並使其得到轉化？為回答上述問題，研究者以大學鄰近深受重工業汙染影響的社區作為本課程的「提問」，把學生認為「太過龐大」的氣候變遷議題聚焦於「減少工業碳排放、促進工業轉型」的在地工業汙染議題。其次，透過「批判的五感教育學」將身體感官置於學習中心，讓學生參與記者會與田野調查，感受社區居民生活與環境運動，使學生從過往囤積式教育的無感學習得到轉化，開始將所學與生活經驗及當地特定脈絡連結，對環境議題有感並形成批判知識。期末學生於特定場域劇場展現其對環境不正義的批判意識與劇場中的行動，進而理解採取在地行動減緩氣候變遷之重要。此即為本研究所稱從「無感」學習經驗到「五感」的環境意識啟蒙及批判教育學實踐。本研究最後提出全球氣候正義議題在地化對永續教育的重要性，並結合五感教育與批判教育學，以補充國內批判教育學的實踐研究。 This study forms part of the broader research project “Global Youth (Digital) Citizen-Artists and their Publics: Performing for Socio-Ecological Justice,” with a specific focus on the Taiwan case study. We conducted a sitespecific theatre class on the environment and climate change in a university’s performing arts department. The research addresses two questions: How can concepts of critical pedagogy be practically applied in theatre education? How can such a class, focused on climate and environmental justice, inspire students to engage in critical thinking and transformative action? To explore these questions, we selected a community near the university severely impacted by heavy industrial pollution as the focal point for this class. By examining the challenge of “reducing industrial carbon emissions and promoting industrial transformation,” we aimed to shift students’ perceptions of climate issues from abstract and overwhelming to concrete and locally relevant. Through “critical sensory pedagogy,” we placed sensory experience at the centre of learning. Students engaged with the lived realities of community residents and environmental movements through immersive activities such as press conferences and field trips. This experiential approach moved them beyond passive containers in banking education, empowering them to connect their academic learning with life experience and specific local historical and social contexts, fostering critical awareness of environmental issues. By the semester’s end, students demonstrated a deepened critical consciousness of environmental injustice, staging sitespecific theatre performances that emphasized the importance of local initiatives in addressing climate change. This process exemplifies what we describe as a shift from “indifference” to “environmental conscientization” through critical sensory pedagogy praxis. This paper highlights the importance of localising global climate justice in sustainable education and contributes to the limited practical research on critical pedagogy by integrating sensory pedagogy with critical pedagogy.